Increased neural progenitors in individuals with cerebral small vessel disease - Ekonomou, A.; Johnson, M.; Perry, R. H.; Perry, E. K.; Kalaria, R. N.; Minger, S. L.; Ballard, C. G. (Neuropathology and applied neurobiology, 2012)
A. Ekonomou, M. Johnson, R. H. Perry, E. K. Perry, R. N. Kalaria, S. L. Minger and C. G. Ballard (2012) Neuropathology and Applied Neurobiology38, 344–353 Increased neural progenitors in individuals with cerebral small vessel disease Aims: Recent work has highlighted a significant increase of neural stem/progenitor cells after stroke in humans. In this study, we examined neurogenesis in small vessel disease, a key concurrent pathology in Alzheimer's disease. Methods: We assayed autopsy tissue from 13 vascular dementia patients with small vessel disease and 12 age‐matched subjects without cerebrovascular pathology, undertaking immunohistochemistry in the affected brain area and the subventricular zone with a well‐characterized battery of antibodies to detect neural stem cells/progenitors and immature neurones, as well as choline acetyltransferase immunoreactivity. Results: We showed significant increases ranging from 33% to 92% (P < 0.05) in neural progenitor cells around the areas of microvascular pathology and in the subventricular zone in patients with small vessel disease compared to individuals without cerebrovascular changes, even in patients with severe cerebrovascular disease, as defined by neuropathological assessment. Some of the progenitor cells give rise to immature neurones in the affected areas. These alterations were associated with vascular changes, but were unrelated to the cholinergic deficit observed in the cortex and subventricular zone in these patients, in contrast to other dementias examined such as dementia with Lewy bodies. Conclusions: This study provides evidence for neurogenesis in small vessel disease and may have important implications for the development of new therapies for neurodegenerative diseases.